TWO NEW SPECIES OF FREYCINETIA (PANDANACEAE) FROM MANOKWARI, WEST PAPUA - SINAGA, NURHAIDAH IRIANY (Research Center for Biology, 2010)
SINAGA, N. I. 2010. Two new species of Freycinetia (Pandanaceae) from Manokwari, Papua. Reinwardtia 13(2): 183-187. - Two new species of Freycinetia from Manokwari, Papua were described; Freycinetia gunungmejensis Sinaga and Freycinetia aculeata Sinaga. These two species are placed into two different groups. F. gunungmejaensis is placed in the non imbricate leaves group that has a non imbricate arrangement of leaves, caducous auricle, 1-keeled prophyll at the base of inflorescence, auxiliary or terminal inflorescence, and with cauline leaves on the terminal inflorescence/ Whereas F. aculeata is included in the imbricate leaves group that has an imbricate arrangement of leaves, persistent auricle, without prophyll, terminal inflorescence and without cauline leaves. The differences between these new species and closely related species are discussed below and their description and distributions are provided.